The Effectiveness Of Salvadora Persica In Treating Denture Stomatitis - Clinical Case Report - Nusima Mohamed; Aida Ali; Naabihgotul Nisaaii Mahamad Kolyubi; Norlela Yacob; Wan Nor Syariza Wan Ali (Zes Rokman Resources, 2024)
Non-Indexed Publication